2008
DOI: 10.1080/02508281.2008.11081553
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism SMTEs Opportunities in Northern Thailand: A Solution to Community Development and Resource Conservation

Abstract: SMEs have become a core component of Thailand's economic development strategies, including tourism initiatives. Small and Medium Tourism Enterprises (SMTEs), with an emphasis on ecotourism and community-based tourism, play a vital role in rural and regional transformation, as these places change from primary to tertiary-industry-based economies. In northern Thailand in particular, a growing number of indigenous communities have been turning to ecotourism as an alternative to expanding their commercial agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Those studies suggested that when local people realize the perceived benefits are less than the cost, they may have anti attitudes and behaviors toward tourism development as well as specific groups who are promoting tourism development in their locality. Sitikarn (2008), Timur & Getz (2008), McCool (2009 and Mannon & Glass-Coffin, (2019) have also confirmed that the downsides of tourism are important reasons for the conflicts at destinations. McCool (2009) mentioned that the conflict arises when local people realize that tourism development causes negative effects on their living environment, change cultural values.…”
Section: Conflict Antecedentsmentioning
confidence: 83%
See 1 more Smart Citation
“…Those studies suggested that when local people realize the perceived benefits are less than the cost, they may have anti attitudes and behaviors toward tourism development as well as specific groups who are promoting tourism development in their locality. Sitikarn (2008), Timur & Getz (2008), McCool (2009 and Mannon & Glass-Coffin, (2019) have also confirmed that the downsides of tourism are important reasons for the conflicts at destinations. McCool (2009) mentioned that the conflict arises when local people realize that tourism development causes negative effects on their living environment, change cultural values.…”
Section: Conflict Antecedentsmentioning
confidence: 83%
“…Residents gathered around the business gate area to protest and boycott tourism businesses. Sitikarn (2008) also mentioned that more than 70% of revenue belongs to private entrepreneurs, which leads to frustration in community.…”
Section: Residents -Tourism Enterprises Conflictmentioning
confidence: 99%
“…CBT is not only a tourism planned, developed, owned and managed by the community for the community but is seen as a new approach to stakeholder involvement and participation in tourism initiatives [26].…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, destinations are regarded as well-defined geographical areas, such as a country, an island or a town [3,4]. In addition, Sitikarn (2008) [5] purposes a model of sustainable Small Medium Tourism Enterprise (SMTEs) that emphasizes on various aspects of human resource development, finance, operation of tourism products and services, marketing and tourists 'demand.…”
Section: Literature Reviewmentioning
confidence: 99%